Immediate Effects of Yoga Based Relaxation Technique on Heart Rate Variability in Young and Healthy Volunteers - Praghosh Chhetri; Lava Shrestha; Binaya SJB Rana; Dinesh Banstola; Narayan Bahadur Mahotra (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Cardiovascular autonomic functions are affected by the negative influences of stress which bring about alterations in heart rate variability (HRV). Yoga based relaxation techniques like Yoga Nidra have been found to relieve stress as shown by improved HRV. This study was conducted to assess the immediate effects of a yoga based guided relaxation technique, Yoga Nidra on HRV parameters in young and healthy volunteers.